Gender disparity in German neurosurgery - Forster, Marie Therese; Behrens, Marion; McLean, Anna Cecilia Lawson; Nistor-Gallo, Dorothea; Weiss, Miriam; Maurer, Stefanie (Journal of Neurosurgery, 2022)
OBJECTIVE Despite the rising number of women in higher education and leadership positions, the proportional rise of female neurosurgeons still lags behind these fields. This study evaluates the gender distribution in German neurosurgical departments across all career levels, and is aimed at heightening the awareness of gender disparity and the need for improving gender equality and its related opportunities. METHODS Data on gender distribution across all professional levels in German neurosurgical departments were obtained from departmental websites as well as by email and telephone request. Results were additionally analyzed in reference to hospital ownership type of the neurosurgical departments. RESULTS A total of 140 German neurosurgical departments employing 2324 neurosurgeons were evaluated. The analysis revealed a clear preponderance of men in leadership positions. Only 9 (6.3%) of 143 department heads were women, and there were only 1 (2.4%), 17 (14.5%), and 4 (12.5%) women among 42 vice-directors, 117 chief senior physicians, and 32 managing senior physicians, respectively. Senior physicians not holding a leadership position were female in 23.1%, whereas board-certified neurosurgeons not holding a senior physician position and residents were female in 33.6% and 35.0%, respectively. Of note, the highest proportion of female department heads (15.6%) was found in private hospitals. CONCLUSIONS The number of women in leadership positions in German neurosurgical departments is dramatically low, and with increasing leadership status gender disparity increases. Mentorship, recruitment, the perception of benefits offered by diversity and programs facilitating gender equality, job sharing, parental leave policies, and onsite childcare programs are needed to turn German neurosurgical departments into modern medical departments reflecting the gender profile of the general patient population.
CRIS-Team Scopus Importer:2022-05-06
Keywords: gender; Germany; neurosurgery; women